(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
From the Universities of the Global South, it is important to generate spaces for reflecting on the didactics of higher education, because based on the content that we select for our courses, the reading that we propose to our students, and the practical activities that we carry out with them, we will contribute to forming tomorrows professionals. An important aspect of their education is that they prepare through a humanist, decolonized and intercultural paradigm. Decolonizing the social sciences and giving a Latin American approach to the courses that we give in the Universities of our region are important tasks in which we should all be involved. This is why we will present some of the pedagogical-didactic experiences that we have been developing over the last six years, in the context of an Anthropology of Education course, carried out in the Department of Anthropology of UNAN-Managua, Nicaragua.